Electronic Procurement Website Service Quality and Customer Loyalty Using The Pieces Method, A Case Study of The Denpasar City Government - IG Wahyu Sanjaya (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
The Denpasar city government uses website facilities to display information on the procurement of goods and services. Publication of information through the website is intended to create a transparent, effective, efficient and accountable procurement system. From it’s initial use since 2013, this system has never been tested to determine whether the system is still in good condition. This study aims to evaluate the system based on user loyalty using the PIECES method. So that the website manager gets input about the quality of the website from the user's point of view. The results of the tests that have been carried out in this study indicate that the Performance Indicators scored 4.2 in the Very Satisfied category, the Information Indicators obtained a value of 4.2 in the Very Satisfied category, Economic Indicators obtained a value of 4.1 in the Satisfied category, Control and Security Indicators obtained a value of 4.3 in the Very Satisfied category, the Efficiency indicator got a score of 4.3 in the Very Satisfied category, the Service indicator got a score of 4.2 in the Very Satisfied category.